Plasmon Enhanced Terahertz Emission from Single Layer Graphene - Bahk, Young-Mi; Ramakrishnan, Gopakumar; Choi, Jongho; Song, Hyelynn; Choi, Geunchang; Kim, Yong Hyup; Ahn, Kwang Jun; Kim, Dai-Sik; Planken, Paul C. M (ACS nano, 2014)
We show that surface plasmons, excited with femtosecond laser pulses on continuous or discontinuous gold substrates, strongly enhance the generation and emission of ultrashort, broadband terahertz pulses from single layer graphene. Without surface plasmon excitation, for graphene on glass, ‘nonresonant laser-pulse-induced photon drag currents’ appear to be responsible for the relatively weak emission of both s- and p-polarized terahertz pulses. For graphene on a discontinuous layer of gold, only the emission of the p-polarized terahertz electric field is enhanced, whereas the s-polarized component remains largely unaffected, suggesting the presence of an additional terahertz generation mechanism. We argue that in the latter case, ‘surface-plasmon-enhanced optical rectification’, made possible by the lack of inversion symmetry at the graphene on gold surface, is responsible for the strongly enhanced emission. The enhancement occurs because the electric field of surface plasmons is localized and enhanced where the graphene is located: at the surface of the metal. We believe that our results point the way to small, thin, and more efficient terahertz photonic devices.